Determinants of productivity growth in the Malaysian food processing industry - Danawir Sultan Bhakti, Yodfiatfinda (2012)
Malaysia is a net importer of food products for the last two decades. Value of imported food grew from RM 8.2 billion in 1996 to RM 28 billion in 2008; spawning a larger trade deficit of RM 10.1 billion compared to RM 4.2 billion in 1996 (MIDA,2010). Demand for processed food in Malaysia is on the rise. The increasing trend is likely to be driven by rapid population growth, higher disposal income, improvement in the living standards, better education and information about health nutrition. The government of Malaysia in its effort to reduce the trade deficit introduced a new agricultural program in the Ninth Malaysia Plan. The plan geared towards changing the orientation of Malaysia agricultural to produce the higher value added and commercially-oriented products. Food processing industries (FPI) generates higher value added for agricultural commodities as it converts raw material from agricultural farm to intermediate inputs or readily consumed products. Food processing industries with controlled and hygiene safe environments transform the product to be more hygienic and, therefore, marketable with prolong expiration date and far-reaching accessibility. This is a crucial cycle in the agribusiness system that is to deliver agricultural products from the raw materials in the farm to readily made products for consumers. The present study investigates efficiency and productivity growth of the Malaysian FPI and identifies its determinants during the period of 2000-2006. The format of the analysis is a two-stage study design. The first stage uses non-parametric approach (data envelopment analysis - DEA) to investigate the efficiency and productivity growth of the Malaysian FPI. The second stage uses tobit regression method to identify determinants of productivity growth. Malaysian FPI can be divided into two groups: small and medium enterprise (SMEs) and large-scale enterprises (LSEs). In the present study, the average technical efficiency (TE) in the SMEs is 75.6 percent based on constant returns to scale (CRS) and 95.4 percent based on variable returns to scale (VRS) during the period of observation. The technical efficiency (TE) value of 75.6 signified the ability of the SMEs to expand their output by as much as 24.4 percent using the same quantity of input. TE in the LSEs was 0.683 based on CRS and 0.952 VRS, means the industry potentially can increase output as much as 31.7% using the same quantity of input. Total factor productivity growth (TFPG) in the SMEs was a mere negative 1.3 percent, contributed by technical efficiency change (EFFCH) value of 1.3 percent and technological change (TECH) value of -2.6 percent. In stark difference to the SMEs,TFPG for the LSEs was a healthy 7.3 percent, contributed by EFFCH value of 3.1 percent and TECH value of 4.2 percent. The findings revealed crucial information about foremost problems faced by the SMEs, i.e., TECH factor, during the period of observation. On the other hand, TECH was the main contributor to a positive TFPG in the LSEs. High-productivity growth is an indication that the industries have efficient production, excellent management perform and high profitability. Therefore, the study identified high productivity growth industry as the highly potential sub-industry in the Malaysian FPI. The high-valued TFPG sub-industries in the SMEs were companies involved in the manufacturing of palm oil, refined palm oil, noodle and snack and, processing and preserving of poultry and poultry products. The subindustries with low-valued TFPG and needed attention for improvement were companies involved in the manufacturing of tea, starch, palm kernel oil, glucose and milk. In the LSEs, the high-valued TFPG sub-industries were companies involved in the manufacturing of alcohol, flour, oil from other vegetables, palm kernel oil and processing and preserving meat and other meat products. The sub-industries that needed attention because of low-valued TFPG were companies involved in the manufacturing of chocolate and, processing and preserving of poultry and poultry products. For these lower TFPG sub-industries, improvement strategies should be formulated by the government at the national level and by the management at the firm level. From the theoretical framework, the study managed to identify the endogenous and exogenous factors affecting the productivity growth. For the SMEs, the study identified four positive determinants of productivity growth. The determinants were R&D (affecting TECH and TFPG), public infrastructure (affecting EFFCH, TECH and TFPG), foreign direct investment (affecting EFFCH, TECH and SECH), and foreign ownership which affecting all dependent variables. Negative determinant of productivity growth was openness (affecting TFPG and TECH). Determinants of productivity growth for the LSEs were training cost (affecting TECH, EFCH and SECH), IT expenditure (affecting EFFCH and TFPG), openness (affecting EFFCH and SECH), and foreign ownership which affect all dependent variables. The negative factors were non-university graduate labor (for SECH and EFFCH) and energy price (for TFPG). The process of improving efficiency and productivity growth of the Malaysian food processing industry is a long-term strategic plan to develop and promote the domestic-food production. The benefits were two folds; producing import substitution and increasing value-added products. As identified in the study, four factors, i.e., R&D, FDI, public infrastructure and foreign ownership were crucial determinants of the TFPG in the Malaysian food processing industry.